Comparative Genomic Analysis of Cutibacterium spp. Isolates in Implant-Associated Infections - Anja Erbežnik; Andraž Celar Šturm; Katja Strašek Smrdel; Tina Triglav; Polona Maver Vodičar (Microorganisms, 2023)
Bacteria of the genus Cutibacterium are Gram-positive commensals and opportunistic pathogens that represent a major challenge in the diagnosis and treatment of implant-associated infections (IAIs). This study provides insight into the distribution of different sequence types (STs) of C. acnes, and the presence of virulence factors (VFs) in 64 Cutibacterium spp. isolates from suspected or confirmed IAIs obtained during routine microbiological diagnostics. Fifty-three C. acnes, six C. avidum, four C. granulosum, and one C. namnetense isolate, collected from different anatomical sites, were included in our study. Using whole-genome sequencing and a single-locus sequencing typing scheme, we successfully characterized all C. acnes strains and revealed the substantial diversity of STs, with the discovery of six previously unidentified STs. Phylotype IA1, previously associated with both healthy skin microbiome and infections, was the most prevalent, with ST A1 being the most common. Some minor differences in STs’ distribution were observed in correlation with anatomical location and association with infection. A genomic analysis of 40 investigated VFs among 64 selected strains showed no significant differences between different STs, anatomical sites, or infection-related and infection undetermined/unlikely groups of strains. Most differences in VF distribution were found between strains of different Cutibacterium spp., subspecies, and phylotypes, with CAMP factors, biofilm-related VFs, lipases, and heat shock proteins identified in all analyzed Cutibacterium spp.